John Webster’s Drama “The Duchess Of Malfi”: The Contexts and Contests of Wit - Astrauskienė, Jurgita; Krūminienė, Jadvyga (Respectus Philologicus, 2014)
The paper examines wit as a major, informing and thematically important literary element that enables the readers to penetrate into the deeper realms of imagination and interpretation. The meaning of the term ‘wit’ has changed a lot during the years both in critical and dictionary usage. Therefore, various conceptions of wit from the diachronic perspective are presented and its types in the theatrical discourse are examined. In the discourse of drama wit is generally divided into two main forms: ‘repartee’ and ‘quip’. As repartee it is used to display ones agility or mental superiority over another character in the dialogue taking a form of a verbal contest. As quip it can act as a sharp stroke of wit to announce the speaker’s original opinion or observation. However, both types of wit invoke cleverness as the most important component of a witty utterance. The interest of the authors is particularly directed towards the role of social wit in John Webster’s drama ‘The Duchess of Malfi‘ (1613). This Jacobean drama is often considered the dramatic masterpiece of the early seventeenth-century English stage. The paper aims to reveal the complexity of a witty dramatic discourse by analyzing its technique, contexts and contest characteristics through the examination of witty instances formed in the drama. It gives an exploration of the social context and mechanism of the formation of a witty utterance that has a high social value as it is in Webster’s play where wit serves to convey the language of contest, often resulting in aggression, open mockery, exposing moral corruption and social injustice.